Important issues of improving the provision of information to the activities of migration and citizenship formalization services of internal affairs bodies - Iskandarovna, Turaeva Dildora (Journal of Innovation in Education and Social Research, 2024)
This article shows the problems in practice related to persons who have accepted the citizenship of a foreign country without relinquishing the citizenship of the Republic of Uzbekistan and who do not wish to relinquish the citizenship of the Republic of Uzbekistan. Also, proposals for these problems were presented by improving the information exchange databases used by the MIA Migration and Citizenship Service and integrating them with partner organizations.